Research of influence of energy consumption of draft gears on longitudinal forces in the tank car train - D. А. Stupin; V. I. Belyaev (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The influence of increasing energy consumption of center coupler draft gear on changing longitudinal forces during the motion of the train was studied. It was shown that the level of force is greatly reduced when equipping tank cars with draft gears of increased energy consumption (class T2 and T3). Article provides technique and results of train tests obtained during the run of the tank car train equipped with draft gears of T2 and T3 classes, and the same train in the same modes with draft gears of the T0 and T1 classes. On the basis of results of comparison tests not only qualitative, but also quantitative impact assessment of high class draft gears was performed on longitudinal dynamics of the train. The analysis of standards of American, European and Russian Railways in this field is provided, also confirming validity of the existing requirements to the draft gears of automatic couplers for cars of the 1520 mm gauge tracks. On the basis of performed complex of tests, including train and impact tests [1], a conclusion about a big positive effect of use of draft gears of high classes is confirmed.